Hubungan Pijat Bayi Dengan Perkembangan Motorik Kasar - Triananinsi, Nurhidayat; Syarif, Sutrani; Prianti, Ani T; Kamaruddin, Mudyawati; Jalil, Jumirah (POLTEKKES KEMENKES MANADO, 2023)
Background: Motor development is a movement process that directly involves the muscles to move and process innovation which a person is capable of loving his body. WHO states that 20-40% of babies experience delays, while Indonesia reaches 16%. One way that can be used to meet the needs for motor growth is to do massage.Objective: this research foresee that Treatment can improve development motor rough in infants aged 3-4 months at the BPM Dewi Suryani clinic.Method: The research design used an observational analytic survey with a correlation research design and a cross-sectional study approach. The population in this study is the entire research subject with a sampling technique using non-probability sampling which was selected by purposive sampling consisting of 30 respondents. The variable measured in this study was gross motor development.Results: This study shows that the development of gross motor babies after massage is higher than before massage p value = 0.025. meaning that there is an influence on massage on development motor rough on babies